REPRODUCTIVE, SERUM BIOCHEMICAL AND HORMONAL TRAITS OF LOCAL QUAIL IN RESPONSE TO DIETARY SUPPLEMENTATION OF GREEN TEA POWDER - Ismael, Lanja A.; M. Ameen, Edrees (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted on 90 local quail females in six different treatments in order to know the effect of adding green tea powder to the quail diet on the productive, reproductive, biochemical and hormonal characteristics of quail females. The results showed a significant superiority of the birds of the group fed on 1% of green tea powder in hot and cold carcass weight, average egg weight, albumin weight, yolk height and color, and the lowest feed consumption, while the control-treated birds in the number of eggs produced, HDP, ALT, Alkaline and Bilirubin exceeded the other treatments birds. Concerning the lipid profile, blood urea ratio, and AST, the highest significant figures were recorded in the treatment of birds fed a ration to which 3% lipids were added. In contrast, the lowest values ​​for total cholesterol, Tri, VLDL, and blood nitrogen were recorded for birds of the treatment fed at 2% of green tea powder. The results showed that there were significant differences between the six treatment birds in the level of blood hormones, as the highest level of (estrogen), (Ghrelin, leptin, FSH), (T4) and (Growth and LH) were recorded for the control birds, 3% lipid and 1% dried green tea and 2% green tea with 3% lipid, respectively. We conclude from the above that birds fed a supplemented diet of 1% green tea powder were superior in most productive and reproductive traits, especially carcass weight, dressed %, egg weight and internal egg characteristics, compared to other treated birds.